2009
DOI: 10.3109/00365590903127446
|View full text |Cite
|
Sign up to set email alerts
|

Expression of renal aquaporins is down-regulated in children with congenital hydronephrosis

Abstract: The expression of AQP1-4 mRNA and protein abundance is reduced in proportion with the degree of hydronephrosis graded by ultrasound in human congenital HK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Bartter syndrome is perhaps the most surprising diagnosis to underlie secondary NDI. The mechanism is not understood but probably other factors are implicated, including hypokalemia, hypercalciuria, nephrocalcinosis, and high urinary flow and pressure that may cause changes in the expression of AQP2 [ 10 , 11 ]. In fact, hypokalemia is typically associated with decreased AQP2 expression, hypercalciuria affects renal concentrating ability via activation of the calcium-sensing receptor, and nephrocalcinosis may impair water reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Bartter syndrome is perhaps the most surprising diagnosis to underlie secondary NDI. The mechanism is not understood but probably other factors are implicated, including hypokalemia, hypercalciuria, nephrocalcinosis, and high urinary flow and pressure that may cause changes in the expression of AQP2 [ 10 , 11 ]. In fact, hypokalemia is typically associated with decreased AQP2 expression, hypercalciuria affects renal concentrating ability via activation of the calcium-sensing receptor, and nephrocalcinosis may impair water reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…The specific functions of each member of this family are now being slowly mapped by several research labs around the world [666] . Their clinical role in cancer [667] , [668] , [669] , [670] , [671] , [672] , [673] , [674] , [675] ,obesity [676] , malaria [677] , [678] and other diseases is emerging [657] , [679] , [680] , [681] , [682] , [683] , [684] , [685] , [686] , [687] , [688] , [689] . In [690] , our group observed the dowregulation of AQP3 in all melanoma cell lines studied of the NCI-60 dataset of Ross et al; this dowregulation was also observed for the CNS and Renal cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced renal aquaporin expression in experimental UUO is noted within 24 h of complete obstruction [ 134 ]. Similarly, renal aquaporins are downregulated in children undergoing pyeloplasty, and in both human and animal models this reduction is associated with polyuria and reduced concentrating ability following relief of obstruction [ 141 143 ].…”
Section: Proposed Molecular Mechanisms Underpinning Pujomentioning
confidence: 99%